Hubungan Karakteristik, Kepuasan Kerja dan Harapan Bidan Terhadap Gaya Kepemimpinan di RSUD Scholoo Keyen Kabupaten Sorong Selatan - Nilawati Uly; M. Ishaq Iskandar; Zamli; Rusmini Kinas (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
Transformational leadership has the ability to encourage employees to achieve results that exceed predetermined expectations. So that transformational leadership can improve the performance of midwives. Job satisfaction is influenced by several factors, namely fair and appropriate remuneration, placement according to skills, the severity of the work, the work atmosphere and environment, equipment that supports the implementation of the work, the leader's attitude and leadership and whether the nature of the work is monotonous or not. To determine the relationship between characteristics, job satisfaction and expectations of midwives on leadership styles at Scholoo Keyen Regional Hospital, South Sorong Regency in 2024. This research is analytical research because it is observing the relationship between research variables and testing hypotheses, with a data collection time approach using a design cross section (Cross Sectional). This research was conducted in April-May 2024 at Scholoo Keyen Regional Hospital, South Sorong Regency. Data collection using questionnaires. A total of 38 respondents said that the leadership style at Scholoo Keyen Hospital, South Sorong Regency was good and 13 respondents said it was not good. A total of 43 respondents said they were satisfied and 8 respondents said they were not satisfied. The Fisher's Exact Test shows that there is a significant relationship between job satisfaction and leadership style at Scholoo Keyen Hospital, South Sorong Regency with a value of p = .000 (p value < .05) so that H0 is rejected and Ha is accepted. There is a relationship between job satisfaction and leadership style at Scholoo Keyen Hospital, South Sorong Regency.